2021
DOI: 10.1111/acer.14673
|View full text |Cite
|
Sign up to set email alerts
|

Disruptions in global network segregation and integration in adolescents and young adults with fetal alcohol spectrum disorder

Abstract: Background: Fetal alcohol spectrum disorder (FASD) is a significant public health problem that is associated with a broad range of physical, neurocognitive, and behavioral effects resulting from prenatal alcohol exposure (PAE). Magnetic resonance imaging (MRI) has been an important tool for advancing our knowledge of abnormal brain structure and function in individuals with FASD. However, whereas only a small number of studies have applied graph theory-based network analysis to resting-state functional MRI (fM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 74 publications
2
4
0
Order By: Relevance
“…In contrast to the many reports of decreased sFNC from fMRI data in various networks in participants with an FASD (Fan et al, 2017; Little et al, 2018; Long et al, 2018, 2020; Santhanam et al, 2011), the dFNC global meta‐state metrics from MEG data reported here indicate increased dynamic fluidity and dynamic range in participants with an FASD. This finding is in line with previous FASD studies which have found increases in global measures of cortical network connectivity such as increased characteristic path length in children with PAE (Wozniak et al, 2013, 2017), and disruptions in global network segregation and integration (i.e., averaging clustering coefficient characteristic path length and global efficiency) in adolescents an FASD (Rodriguez et al, 2021). There are important temporal differences between MEG and fMRI resting‐state data (i.e., MEG data have a higher temporal resolution and may provide connectivity patterns unique from fMRI) and distinctions between global meta‐state information and network correlations (i.e., how participants travel through states versus direct network to network correlations) which should be considered when comparing findings.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In contrast to the many reports of decreased sFNC from fMRI data in various networks in participants with an FASD (Fan et al, 2017; Little et al, 2018; Long et al, 2018, 2020; Santhanam et al, 2011), the dFNC global meta‐state metrics from MEG data reported here indicate increased dynamic fluidity and dynamic range in participants with an FASD. This finding is in line with previous FASD studies which have found increases in global measures of cortical network connectivity such as increased characteristic path length in children with PAE (Wozniak et al, 2013, 2017), and disruptions in global network segregation and integration (i.e., averaging clustering coefficient characteristic path length and global efficiency) in adolescents an FASD (Rodriguez et al, 2021). There are important temporal differences between MEG and fMRI resting‐state data (i.e., MEG data have a higher temporal resolution and may provide connectivity patterns unique from fMRI) and distinctions between global meta‐state information and network correlations (i.e., how participants travel through states versus direct network to network correlations) which should be considered when comparing findings.…”
Section: Discussionsupporting
confidence: 91%
“…, the dFNC global metastate metrics from MEG data reported here indicate increased dynamic fluidity and dynamic range in participants with an FASD. This finding is in line with previous FASD studies which have found increases in global measures of cortical network connectivity such as increased characteristic path length in children with PAE(Wozniak et al, 2013(Wozniak et al, , 2017, and disruptions in global network segregation and integration (i.e., averaging clustering coefficient characteristic path length and global efficiency) in adolescents an FASD(Rodriguez et al, 2021). There are important temporal differences between MEG and fMRI resting-state data (i.e., MEG data have a higher tem-…”
supporting
confidence: 91%
“…The authors then followed this with a meta-analysis demonstrating that the hubs of the human connectome were more likely to contain gray matter lesions than non-hub regions across nine different disorders, including schizophrenia and Alzheimer’s disease. Many psychiatric and neurological disorders are associated with reduced brain global efficiency, including prenatal alcohol exposure ( Wozniak et al, 2013 ) and fetal alcohol syndrome ( Rodriguez et al, 2021 ), schizophrenia ( Hummer et al, 2020 ), ADHD ( Wang et al, 2020 , 2021 ), generalized anxiety disorder ( Guo et al, 2021 ), heavy smoking ( Lin et al, 2015 ), and major depressive disorder (( Meng et al, 2014 ); Wang et al, 2017 ; Zhi et al, 2018 ), among others. Additionally, prefrontal tDCS for alcohol use disorder increased brain network global efficiency ( Holla et al, 2020 ), suggesting that normalizing network global efficiency might contribute to improved treatment outcomes from neuromodulation therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The authors then followed this with a meta-analysis demonstrating that the hubs of the human connectome were more likely to contain grey matter lesions than non-hub regions across nine different disorders, including schizophrenia and Alzheimer’s disease. Many psychiatric and neurological disorders are associated with reduced brain global efficiency, including prenatal alcohol exposure (Wozniak et al, 2013) and fetal alcohol syndrome (Rodriguez et al, 2021), schizophrenia (Hummer et al, 2020), ADHD (Wang et al, 2020; Wang et al, 2021), generalized anxiety disorder (Guo et al, 2021), heavy smoking (Lin et al, 2015), and major depressive disorder (Meng et al, 2013; Wang et al, 2017; Zhi et al, 2018), among others. Additionally, prefrontal tDCS for alcohol use disorder increased brain network global efficiency (Holla et al, 2020), suggesting that normalizing network global efficiency might contribute to improved treatment outcomes from neuromodulation therapy.…”
Section: Discussionmentioning
confidence: 99%